Ethnic Diversity and National Cohesion in Nepal: Addressing Contested Identities (Panauti Journal, 2025)
The issue of identity has played a significant role in shaping Nepal’s political and social dynamics. This term paper examines ethnic diversity and national cohesion in Nepal. The study draws on scholarly articles and other relevant publications. The primary focus is on the growing tension between ethnic diversity and national integration, which has contributed to the emergence of contested identities in Nepal’s nation-building efforts. For this research, relevant literature and publications were gathered from secondary sources. A descriptive and interpretive methodology was employed to achieve the study’s objectives. The findings reveal that minority languages and cultural practices in Nepal have historically been marginalized, resulting in inequality and contested identities. Additionally, geographic and structural factors have intensified disparities among ethnic groups. The study emphasizes that promoting equal recognition of languages, cultures, and opportunities—together with inclusive policies and awareness programs—is vital for strengthening national integration and fostering social cohesion. It recommends that inclusive language policies, equitable access to resources and opportunities, and intercultural initiatives are essential strategies for reducing contested identities and supporting sustainable national integration in Nepal.